PEMANFAATAN DTMF (DUAL TONE MULTIPLE FREQUENCY)SEBAGAI INDIKATOR KONDISI INFUS SECARA WIRELESS - Danang Padmadi dan Fatchurrohman (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research aims at knowing the benefit of DTMF in reporting theinfus condition. To show if infus runs out, DTMF uses the frequencyinformation. Then, the frequency will be modulated to be emitted. Thedesign system is like radio or tv transmitter. The patient room will be thetransmitter of the infus condition and the monitor room is as the informationreceiver, in which the data are frequency information. In the receiver, thefrequency codes are tranferred into binary codes. Those codes are proceededas appearance showing the infus number.The utilization design of DTMF can be used in hospital. This device iseffective in the condition that infus is motionless since it uses spring censor.The spring must be the best quality one. The censor will be active when infusis 20cc.This research has not been completed since there are failures. It isdesigned to continue the research on the utilization of DTMF. The success ofthis research will be continued with the application of this research inhospital.Key words: DTMF, The utilization of DTMF